Spatial analysis of Toxocara spp. eggs in soil as a potential for serious human infection. (April 2021) - Raissi, Vahid; Masoumi, Mohammad taqi; Ibrahim, Asmaa; Etemadi, Soudabeh; Getso, Muhammad; Jalali, Pantea; Babaei Pouya, Navid; Zareie, Mohammad; Ehsani Amraei, Fatemeh; Raiesi, Omid
Highlights: Examination of soil can be used to estimate the risk of parasitic infection in humans. We carried out this survey to clarify the current status of soil contamination by Toxocara eggs. The spatial distribution of Toxocara spp. was analyzed in relation with cats and dogs' frequency. Overall contamination of soil samples by Toxocara eggs. reached 18.3 %. According to the results obtained, marginal areas are often contaminated with eggs of Toxocara spp. From the results obtained, the need for health education with regards to zoonoses was revealed. Abstract: Toxocara spp. cause one of the most widespread soil-transmitted helminthic infections worldwide. In both developed and developing countries, soil contamination with Toxocara eggs is considered as a major threat to public health. A total of 515 soil samples from 89 sampling sites were collected from different locations of public health such as Wastelands and Streets, public parks, and marginal areas. The soil samples were examined for Toxocara eggs using a centrifugal-floatation technique utilizing a saturated sodium nitrate solution. centralization of positive soil samples in the province was studied by Spatial Statistics Techniques such as Average Nearest Neighbors and Spatial Autocorrelation and Kernel Density Function Toxocara spp. eggs were found in 94 (18.25 %) out of 515 samples collected from the studied areas. According to the results obtained, marginal areas are often contaminated with eggs of Toxocara . Consequently, preventive measures including health education should be implemented to reduce the potential risk of this parasitic infection.